The effect of fatigue in elite young female wrestlers upon balance performance and reaction - Iri, R.; Burak Aktug, Z.; Koc, M.; Sahin, I.; Murathan, F. (Biomedical Research, 2016)
The purpose of the study was to investigate the effect of fatigue in Turkish National Team Young Female Wrestlers upon balance performance and reaction time. Totally 17 female wrestlers with 18.58 ± 2.26 years age average, 165.65 ± 6.88 cm height average, 62.55 ± 9.35 kg weight average, and 22.53 ± 2.03 kg/m2 body mass index were included into the study voluntarily. The wrestlers participated into the research were asked to make a match in accordance with the real conditions. Static-dynamic balance performance and reaction time tests were performed to the female wrestlers as rested before and as fatigue after the match. Static-dynamic balance measurements of the wrestlers were determined using Biodex Balance System, visual reaction time measurements were determined using MOART Lafayette Reaction Measurement Device, and fatigue levels were determined using handheld Lactate analyser. Whereas negative relationship (p<0.005, r=-0.577) was found between after match (fatigue) lactate level and after match static balance (p<0.005, r=-0.505) and dynamic balance, after match lactate level was determined not to have a significant relationship with after match reaction time (p>0.005, r=0.395). Consequently, the balance skill as one of the most important requirements of high performance in wrestling was determined to deteriorate through the increase at fatigue level. Moreover, although no significant relationship was found between fatigue and reaction time, the time for fatigue reaction time was noticed to be higher rather than rested reaction time.